DAMPAK PRAKTIK BANK TITHIL TERHADAP KESEJAHTERAAN EKONOMI MASYARAKAT DALAM PERSPEKTIF EKONOMI ISLAM - Dewi Kumalasari; Suyitno (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2024)
This study aims to analyze the impact of bank tithil practices on the economic welfare of society and examine them from the perspective of Islamic economics. Using a descriptive qualitative approach through interviews and observations in Banjar Village, the study found that bank tithil practices provide easy access to capital but create dependency, high interest burdens, and a decline in welfare. From an Islamic perspective, this practice contains elements of riba and contradicts the principles of justice, mutual assistance, and overall welfare (falah).